#### Answer

y=4

#### Work Step by Step

Simplifying
3y + -5(2 + -1y) = 22
3y + (2 * -5 + -1y * -5) = 22
3y + (-10 + 5y) = 22
Reorder the terms:
-10 + 3y + 5y = 22
Combine like terms: 3y + 5y = 8y
-10 + 8y = 22
Solving
-10 + 8y = 22
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '10' to each side of the equation.
-10 + 10 + 8y = 22 + 10
Combine like terms: -10 + 10 = 0
0 + 8y = 22 + 10
8y = 22 + 10
Combine like terms: 22 + 10 = 32
8y = 32
Divide each side by '8'.
y = 4
Simplifying
y = 4